Burnout pada Tenaga Kesehatan di Kabupaten Karawang: Peran Dukungan Sosial dan Perceived Stress - Pratomo, Bimo; Dimala, Cempaka Putrie; Pertiwi, Anggun (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2024)
This study aims to examine the effect of social support and perceived stress on burnout in health workers in Karawang Regency. Participants in this study were early to late adults aged 20 to 45 years and domiciled in Karawang Regency with a total of 102 participants, the method used was quantitative with causality design and cluster sampling technique. Data were collected through psychological scales that measure variables of multidimensional scale of perceived social support (MSPSS), perceived stress scale (PSS), and maslach burnout inventory (MBI). Data analysis was conducted using normality test, linearity test, multiple regression test, and coefficient of determination test with the help of SPSS program. The results showed that the data was normally distributed and both independent variables, namely social support and perceived stress significantly influenced the level of burnout with a significance value of 0.000. The coefficient of determination of social support and perceived stress on burnout is (R Square) 0.249 or 24.9%, where social support and perceived stress contribute 0.005 while perceived stress is 0.000, meaning that these findings indicate the need for interventions aimed at increasing social support and reducing perceived stress to prevent burnout in health workers. Further research is recommended to focus on more specific and contextual intervention strategies according to the needs of health workers in Karawang Regency.